Negative Effect of Biventricular Pacing on Right Ventricular Function: A Case Report - Maragna, Riccardo; Scoccia, Alessandra; Tundo, Fabrizio; Fusini, Laura; Agostoni, Piergiuseppe; Vignati, Carlo (Cardiology and Cardiovascular Medicine, 2020)
Abstract not available in the source database.